Primary Control with Virtual Impedance for a Highly Resistive Autonomous Microgrid - Fernandez-Beltran, M (Institute of Electrical and Electronics Engineers Inc., 2022)
Microgrids are an important topic in the energy systems of the future. Three of the goals of the energy systems are the decentralization, to decarbonize, and democratize. The investigation in this topic has gone too far in many aspects, but there still things the research doesn t count. For expample, the differences in grid profile in different countries, in terms of frequency and voltage of the utility grid. Other issue is that most of the research its done in english, leaving behind a group of learners that wants to enter in the topics of microgrids. In this paper, a three-phase highly resistive low-voltage microgrid is used in which an inductive virtual impedance is implemented, with the aim of observing its behavior within the determinated conditions, like chilean grid profile and a high R/X ratio. © 2022 IEEE.